2017
DOI: 10.1186/s12885-017-3155-2
|View full text |Cite
|
Sign up to set email alerts
|

MEIS1 inhibits clear cell renal cell carcinoma cells proliferation and in vitro invasion or migration

Abstract: BackgroundMyeloid ecotropic viral integration site 1 (MEIS1) protein plays a synergistic causative role in acute myeloid leukemia (AML). However, MEIS1 has also shown to be a potential tumor suppressor in some other cancers, such as non-small-cell lung cancer (NSCLC) and prostate cancer. Although multiple roles of MEIS1 in cancer development and progression have been identified, there is an urgent demand to discover more functions of this molecule for further therapeutic design.MethodsMEIS1 was overexpressed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…A previous study reported higher expression of MEIS-1 in healthy prostate tissues than in prostate carcinoma tissues, and concluded that MEIS-1 may serve as a predictive biomarker of prostate cancer prognosis [ 21 ]. Similar studies reported that MEIS-1 is a suppressor of non-small-cell lung cancer, esophageal squamous cell carcinomas and clear cell renal cell carcinomas [ 14 , 22 25 ]. A recent paper reported that MEIS-1's expression level can predict treatment outcome in HCC patients [ 26 ].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…A previous study reported higher expression of MEIS-1 in healthy prostate tissues than in prostate carcinoma tissues, and concluded that MEIS-1 may serve as a predictive biomarker of prostate cancer prognosis [ 21 ]. Similar studies reported that MEIS-1 is a suppressor of non-small-cell lung cancer, esophageal squamous cell carcinomas and clear cell renal cell carcinomas [ 14 , 22 25 ]. A recent paper reported that MEIS-1's expression level can predict treatment outcome in HCC patients [ 26 ].…”
Section: Introductionsupporting
confidence: 55%
“…For example, aberrant expression of MEIS-1 promoted the development of acute myeloid leukemia [ 15 19 , 35 ]. However, MEIS-1 has been reported as a negative regulator of some other cancers, such as non-small-cell lung cancer, esophageal squamous cell carcinomas, clear cell renal cell carcinomas and prostate cancer [ 22 25 ]. In these studies, the authors proposed that MEIS-1 inhibits tumor cell proliferation and induces cell cycle arrest [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splice variants of Meis1 containing Meis1a and Meis1b found in human and mice and two new Meis1d transcripts were found with 27 kD weight (Meis1 27 ) in cytoplasm of proximal colon epithelial cells and the Meis1 32 kD variant (Meis1 32 ) in the nuclei of non-epithelial cells in the stomach and colon; finding various Meis1 variants in different cell types and subcellular compartments [64]. This may explain the contradictory findings that Meis1D, the homeodomain-less splice variant of Meis1, is found to inhibit gastric [65] and clear renal cell carcinogenesis [66], or to be downregulated in colorectal carcinomas, suggesting that Meis1D is a tumor suppressor [64].…”
Section: Pathogenic Stimulusmentioning
confidence: 99%
“…PREP1 has been associated with induction of cell transition and cancer spread through the TGF-b/ SMAD3 pathway in non-small cell lung carcinoma (NSCLC) [71]. As Meis1 was reported to induce G1/2 arrests and non-apoptotic cell death through decreased levels of Survivin and B-cell lymphoma 2 (Bcl-2) [66], its non-oncogene effect might be a matter of concentration which, in turn, argues in favor of the disruption-of-homeostasis concept in carcinogenesis. Meis1 associated cell growth promotion is directly linked to RB1 cell-cycle signaling [72].…”
Section: Pathogenic Stimulusmentioning
confidence: 99%